Moderate and Severe Level of Food Insecurity Is Associated with High Calorie-Dense Food Consumption of Filipino Households - Imelda Angeles-Agdeppa; Marvin B. Toledo; Jezreel Ann T. Zamora (Journal of Nutrition and Metabolism)
Food insecurity is often deeply rooted in poverty. Hence, accessibility and the quality of foods consumed may affect the dietary pattern. The study aims to assess the relationship between food insecurity and dietary consumption. This investigation analyzed the data from the 2015 Updating of Nutritional Nutrition Survey. The Household Food Insecurity Access Scale (HFIAS) was used to determine household food security status and the prevalence of food insecurity. Food weighing, food inventory, and food recall were the methods used to collect food consumption data of sampled households. The study revealed poor nutrient quality and a greater likelihood of inadequacy of nutrients among moderate and severe food insecure households. Mild, moderate, and severe levels of food insecurity were found to affect 12%, 32%, and 22% of the population, respectively. The test showed that both moderate and severe food insecure families have significantly lower mean consumption of meat, milk, and fats and oils in contrast to food secure households. In comparison with food secure households, moderate and severe food insecure households consume higher amounts of cereals and cereal products, rice, and vegetables. Moderate and severe food insecure households have higher consumption of total carbohydrates but have significantly lower average intake of vitamin A, riboflavin, niacin, and total fat related to food stable households. Moreover, the results of the multiple logistic regression revealed that food insecure households have a higher likelihood to be deficient in energy, protein, calcium, vitamin A, thiamin, riboflavin, niacin, and vitamin C intakes, but except for iron (p value <0.05). Indeed, household food insecurity was associated with the higher consumption of calorie-dense food among Filipino households. This explains a lower nutrient quality and a higher likelihood of inadequacy of nutrients among moderate and severe food insecure households.